Curcumin and Natural Derivatives Inhibit Ebola Viral Proteins: An In silico Approach - Shruti Baikerikar (Pharmacognosy Research, 2017)
Background: Ebola viral disease is a severe and mostly fatal disease in humans caused by Ebola virus. This virus belongs to family Filoviridae and is a single‑stranded negative‑sense virus. There is no single treatment for this disease which puts forth the need to identify new therapy to control and treat this fatal condition. Curcumin, one of the bioactives of turmeric, has proven antiviral property. Objective: The current study evaluates the inhibitory activity of curcumin, bisdemethoxycurcumin, demethoxycurcumin, and tetrahydrocurcumin against Zaire Ebola viral proteins (VPs). Materials and Methods: Molecular simulation of the Ebola VPs followed by docking studies with ligands comprising curcumin and related compounds was performed. Results: The highest binding activity for VP40 is −6.3 kcal/mol, VP35 is −8.3 kcal/mol, VP30 is −8.0 kcal/mol, VP24 is −7.7 kcal/mol, glycoprotein is −7.1 kcal/mol, and nucleoprotein is 6.8 kcal/mol. Conclusion: Bisdemethoxycurcumin shows better binding affinity than curcumin for most VPs. Metabolite tetrahydrocurcumin also shows binding affinity comparable to curcumin. These results indicate that curcumin, curcuminoids, and metabolite tetrahydrocurcumin can be potential lead compounds for developing a new therapy for Ebola viral disease.
Keywords: Bisdemethoxycurcumin; Curcumin; Demethoxycurcumin; Docking; Ebola virus; Tetrahydrocurcumin